(untitled) (Academicia Globe: Inderscience Research, 2021)
Carefully observing the architectural structures and complexes, urban-planning ensembles and creative works created during the years of independence of the Samarkand region and the city, we feel the harmony of their inherent wonders and natural landscapes, intermediate, consistent architectural order, high architectural order and a high architectural sense of folk applied art. Unfortunately, these important and high architectural qualities are currently insufficient for the environment of buildings and structures created in some cities, district centers and villages.